Impact of cattle night corralling on soil properties and vegetation in the semiarid degraded rangeland of Ethiopia (Bangladesh Journal of Animal Science, 2022)
In Ethiopia, rangeland degradation is a severe environmental problem. To improve rangeland vegetation cover and support the rangeland-based livelihoods, it is imperative to repair degraded rangeland using different rehabilitative measures. This study was carried out to evaluate the effects of night cattle corralling impact on soil chemical parameters, herbaceous species compositions and biomass yield of degraded rangeland.  To conduct the experiment, severely degraded (SD) and moderately degraded (MD) rangelands with an area size of 30m x10m (300m2) each was identified. Then, each of the selected rangeland types was separated into two paddocks with an area size of 10m x 15m (150 m2). The treatment paddocks of the severely and moderately degraded rangeland were treated by cattle impact tools corralling cattle every night in the paddock for one month (SDT1 and MDT1). While the second paddock in both rangeland types was used as a control without cattle impact tools (SDT2 and MDT2). A randomized complete block design was used and each treatment was replicated three times. The results showed that soil chemical parameters and herbaceous species compositions in both degraded rangeland paddocks treated with cattle impact tools (SDT1 and MDT1) changed significantly (p